Estabilidade de suco de uvas 'BRS Magna' colhidas em diferentes sistemas de condução e porta-enxertos no Vale do São Francisco - Félix, Liliane Dária (2020)
The production of grape juices in the São Francisco River Valley has increased significantly in recent years, due to the growing demand for the product, which has high acceptability, in addition to being a functional drink. ‘BRS Magna’ is one of the main grape cultivars used to make juices, since its berries stand out by their high levels of anthocyanins, soluble solids and raspberry-like flavor and aroma, ideal for obtaining the desired color, sweetness and flavor for the product. Therefore, the implementation of this cultivar in the region is recent, so few technical-scientific data have been reported regarding the influence of management practices on the quality and stability of the juice of this variety. Thus, the aim of this study was to determine the stability of physicochemical attributes, color, phenolic compounds and antioxidant capacity of juices made with grapes 'BRS Magna' grown in different trellis systems, in rootstocks ‘IAC 572’ and ‘IAC 766’. The juices were produced with grapes 'BRS Magna' (100%) using the steam extraction method and evaluated in three storage times (0, 6 and 12 months) for physicochemical characteristics: soluble solids, reducing sugars, titratable acidity, volatile acidity, alcohol content, pH, turbidity and density. Additionally, color and tone of the juice were analyzed by spectrophotometry and by CIELab and CIEL*C*h systems. Levels of 27 phenolic compounds, including monomeric anthocyanins, flavanols, flavonols, phenolic acids and stilbenes, were quantified by high performance liquid chromatography. The antioxidant capacity was quantified by three methods, DPPH, ABTS and FRAP. Physicochemical quality of the juices remained stable after 12 months of storage, and all samples fit the quality standards by the Brazilian legislation for whole grape juice. However, significant changes have been observed in the color and tone of the products, in both rootstocks, and in turbidity in ‘IAC 572’. Phenolic compounds content changed during storage, with a pronounced decrease of all quantified monomeric anthocyanins and (+)-catechin and (-)-epicatechin, in both rootstocks. The reduction in the content of these compounds over the shelf life is possibly related to the decrease in the antioxidant capacity of the juices, decreasing their nutritional quality, regardless the trellis system or rootstock adopted for the vines. On the other hand, storage promoted an increase in the concentrations of most phenolic acids evaluated and of Procyanidin B2, in both rootstocks. The juices showed a reduction in antioxidant activity throughout the shelf life, regardless of the trellis system adopted for the vine. For the ‘IAC 572’ rootstock, the vertical shoot positioning trellis system is recommended for providing ‘BRS Magna’ juices with a higher content of soluble solids, better coloration, higher content of phenolic compounds, mainly anthocyanins, and greater antioxidant capacity. On the other hand, the overhead trellis system is the most suitable for the production of juices with 'BRS Magna' grapes conducted on the 'IAC 766' rootstock, since this trellis system provides the juices with a higher content of soluble solids, greater content of phenolic compounds, especially anthocyanins, and greater antioxidant capacity.